Narasi Ilmu Pengetahuan dalam Novel Erni Aladjai Haniyah dan Ala di Rumah Teteruga - Latifah, Suci Ayu (Jurnal Bahasa dan Sastra, 2024)
Science is the source or result of a thought. In literary works, science is used by authors to produce works of quality, quality, and competitiveness. The novel Haniyah and Ala at Teteruga’s House spreads knowledge about various things. Therefore, it is interesting to study more deeply using the theory of literary ecoanthropology. Anthropological theory and literary ecology will be combined as a multidisciplinary study. The novel reveals the history of the 1950s and 1990s regarding clove farmer conflicts. The descriptive qualitative method is intended to describe the narrative of science in the novel’s research object. Data collection uses the technique of watching, reading, and taking notes, resulting in scientific findings about: (i) the life of clove farmers, (ii) the lifestyle of the people in Kon Village, (iii) flora and fauna, (iv) natural resources for human needs life, (v) how to plant and harvest clove trees, (vii) traditional items, and (viii) folklore.